Presentation - Mansilla, Ricardo (INTER DISCIPLINA, 2020)
The works that appear in this issue show different lines of research where their models are inspired by the critical phenomena of physics. The panorama shown is very wide: from a proposal of critical self–organization for natural languages, to the ubiquity of certain power laws in the structure of living beings. We hope you enjoy them.